Percolative model and thermodynamic analysis of oxygen-ion-mediated resistive switching - Raghavan, Nagarajan (2013)
We present a statistical percolation model for retention lifetime assessment of resistive switching memory at the high-resistance state and correlate it to the soft breakdown phenomenon in ultrathin gate dielectrics. Electrical characterization in the low-resistance state shows that the location of oxygen-vacancy-based conductive filaments is almost randomly distributed and the trap generation rate across the oxide after reset transition is uniform. The constraints for the range of read voltages in the low and high conduction states, governed by the area of the device and the thermodynamics of oxygen ion transport, are presented.